Students' Perceptions of Using Zoom Meeting to Improve Speaking Skills during Online - Arina Chusnatayaini (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The change in learning systems from face-to-face interactions in classrooms to online learning systems during the Covid-19 pandemic is having a profound impact on the learning process. A variety of learning activities should be presented for the continuation of the learning process. These changes lead to different learning needs of students. This study explores student perceptions of using Zoom Meeting for online learning in teaching English speaking skills. The study has been conducted at IIK STRADA Indonesia. Students of the third semester were chosen as the respondents of this study selected by using purposive sampling. The data were obtained from questionnaires and interviews. The questionnaire was distributed using Google Form. As a result, the researcher found that students can easily understand some language learning materials by using Zoom meetings. However, in other cases, most of the students were bored with implementing online courses and suffered from lack of motivation to study during the COVID-19 pandemic. In summary, the student expressed positive and negative attitudes towards using Zoom Meeting for online learning in teaching English speaking skills. Keywords: zoom meeting application, speaking skill, online learning.